Social and Digital Expressions in Urdu Literature: A Critical Study and Intellectual Dimensions - Aslam, Sajida (Makhz (Research Journal), 2025)
In the contemporary era, Urdu literature is no longer confined to printed books and traditional publishing channels. Digital and social media platforms have expanded its modes of expression, dissemination and interpretation. Online journals, e-books, literary websites, Facebook fiction, Instagram visual poetry and YouTube videos have together created an electric literary environment that is immediate, visual and publicly accessible. These new literary forms are not merely expressions of personal emotion or entertainment; rather, they foreground pressing social and environmental issues such as gender inequality, class disparity, minority rights, pollution, climate change and water scarcity as central themes of literary engagement. Social media has enabled direct dialogue between reader and writer and it has allowed a new generation to actively participate in literary and critical processes. These writings exhibit a blend of protest aesthetics, intellectual awakening and a yearning for transformation. Although social media literature differs from traditional literary forms in many ways, its social engagement, thematic diversity and role in shaping the intellectual development of younger readers are undeniable. This paper offers a critical exploration of these emerging digital literary practices and identifies a new, dynamic and socially conscious narrative evolving within contemporary Urdu literature.